KEANEKARAGAMAN JENIS TUMBUHAN PAKU (PTERIDOPHYTA) DI KAWASAN HUTAN TUMBANG MANGGU, KECAMATAN SANAMAN MANTIKEI, KABUPATEN KATINGAN, KALIMANTAN TENGAH - Sri Hartini (Universitas Pakuan, 2020)
Research on the diversity of ferns in the forests of Tumbang Manggu, Sub-district Sanaman Mantikei, Central Kalimantan, has been done. The study was conducted in March April 2016Â by using explorative methods. The results show, at least 28 species of ferns were found in the forest area, of which 16 species are terrestrial ferns and 12 species of epiphytic ferns. These species are included in 22 genera and 14 families. Huperzia and Pyrrosia are most abundant, each genus were consists of 3 species. The most rich families in term number of species are Polypodiaceae and Lycopodiaceae, with 6 species and 4 species respectively. Abundance of each species in the region was different, Blechnum orientale L., Dicranopteris linearis (Burm. f.) Underw., Lycopodiella cernua (L.) Pic. Serm., and Vittaria scolopendrina (Bory) Schkuhr ex Thwaites were found in large quantities and spread almost all over the region. Asplenium nidus L., Drynaria quercifolia (L.) J. Sm., Stenochlaena palustris (Burm. f.) Bedd., Lygodium circinatum (Burm. f.) Sw., Pyrrosia lanceolata (L.) Farw., Nephrolepis falcata (Cav.) C. Chr. and Vittaria ensiformis Sw. were found in considerable numbers. Asplenium pellucidum Lam., Athyrium bantamense Milde, Helminthostachys zeylanica (L.) Hook. and Tectaria crenata Cav. were found in small quantities and only in certain places. Local communities around the region have not much utilizing the ferns yet.